Cost effectiveness of screening for dengue infection in a UK teaching hospital. Issue 2 (February 2018) - Veater, James; Wong, Nicholas; Lai, Florence Y.; Stephenson, Iain; Wiselka, Martin; Tang, Julian W.
Highlights: Dengue screening in returning travellers with compatible symptoms is routine. However the cost effectiveness may differ between teams from different specialities. Only thrombocytopaenia was significantly correlated with confirmed dengue infection. A geographically-based, reference laboratory screening algorithm aided diagnosis. No clinical speciality was better than any other in diagnosing dengue infection.